Locus of Control and Social Support Analysis of the Need of Achievement, Interests, and Entrepreneurial Attitude of UNISKA Students in the Society 5.0 Era - Mayvita, Prihatini Ade; Lamsah, Lamsah; Shaddiq, Syahrial (Journal of Social Work and Science Education, 2023)
During the pandemic coronavirus disease 2019 (COVID-19), many new entrepreneurs have sprung up, this is because many companies have laid off. In order to prepare intellectuals with entrepreneurial spirit and increase the quantity and quality as well as support government programs, universities need to play a more active role. This research aims to analyze locus of control and social support of the need of achievement, interests, and entrepreneurial attitude of UNISKA students in the society 5.0 Era with method. This type of research used qualitative descriptive research where the key instrument is, purposive and snowball sampling of data sources. The results showed that: (a) Internal, external and social support locus of control, play a role in the interest in entrepreneurship in UNISKA students. (b) Internal, external and social support locus of control play a role in the achievement needs of UNISKA students. (c) Locus of control internal, external and social support plays a role in the entrepreneurial attitude of UNISKA students.